Ультраструктура поверхні листків деяких сортів Syringa vulgaris L. - Zaimenko, N.V.; Ilyinskaya, А.P.; Dovgalyuk, N.I.; Sitnyanskaya, N.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The results of comparative investigation of leaf surface ultrastructure of class Syringa vulgaris L. ‘Ogni Donbassa’ and ‘Krasavitsa Moskvy’ in the norm and under the silicone organic and mineral maturing action in monoculture garden of lilac’s of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine are presented.